Highlights methodology of time characteristics optimization for plastic products production - Matarneh, Rami; Sotnik, Svitlana; Deineko, Zhanna; Lyashenko, Vyacheslav (International Journal of Engineering and Technology, 2018)
Basic elements of casting process and its main stages are considered. Features of time characteristics for production of plastic products are investigated. The main stages in the methodology of time optimization characteristics for the production of plastic products are given. The proposed methodology allows to increase productivity and optimize the time characteristics of the process of production of plastic products, taking into account the preservation of the quality of plastic products which is achieved by reducing the casting cycle. At the same time the considered methodology considers plunger time forward and backward, the "course" of the nozzle time, the time of extraction of the product from the matrix during the production of plastic products.